Mood and Suicidality among Cyberbullied Adolescents: A Cross-Sectional Study from Youth Risk Behavior Survey - Ya-Ching Hsieh; Pratik Jain; Nikhila Veluri; Jatminderpal Bhela; Batool Sheikh; Fariha Bangash; Jayasudha Gude; Rashmi Subhedar; Michelle Zhang; Mansi Shah; Zeeshan Mansuri; Urvish Patel; et al. (MDPI AG, 2021)
Background: There is limited literature available showing the mental health burden among adolescents following cyberbullying. Objective: The aim was to evaluate the association between low mood and suicidality among cyberbullied adolescents. Method: A cross-sectional analysis of the data was performed among adolescents from the National Youth Risk Behavior Surveillance System. Responses from adolescents related to cyberbullying and suicidality were evaluated. Chi-square and mix-effect multivariable logistic regression analysis was performed to determine the association of cyberbullying with sadness/hopelessness and suicide consideration, plan, and attempts. Results: Of a total of 8274 adolescents, 14.8% of adolescents faced cyberbullying past year. There was a higher prevalence of cyberbullying in youths aged 15, 16, and 17 years (25%, 26%, 23%, respectively), which included more females than males (68% vs. 32%; p < 0.0001). Caucasians (53%) had the highest number of responses to being cyberbullied compared to Hispanics (24%) or African Americans (11%; p < 0.0001). There was an increased prevalence of cyberbullied youths, feelings of sadness/hopelessness (59.6% vs. 25.8%), higher numbers considering suicide (40.4% vs. 13.2%), suicide plan (33.2% vs. 10.8%), and multiple suicidal attempts in comparison to non-cyberbullied (p < 0.0001). On regression analysis, cyberbullied adolescents had a 155% higher chance of feeling sad and hopeless [aOR = 2.55; 95%CI = 2.39-2.72] and considered suicide [aOR = 1.52 (1.39-1.66)] and suicide plan [aOR = 1.24 (1.13-1.36)]. Conclusion: In our Study, cyberbullying was associated with negative mental health outcomes. Further research is warranted to examine the impact of cyberbullying among adolescents and guiding the policies to mitigate the consequences.